Manajemen Layanan Teknologi Informasi Perusahaan Perseroan Menggunakan Information Technology Infrastructure Library Service Operation: Literature Review - Tjonadi, Callista; Wijaya, Khellyn Viorensa; Roselin, Vanesia; Natalie, Vellyn; Maulana, Ade (JDMIS: Journal of Data Mining and Information Systems, 2023)
At this time, information technology is growing rapidly in various business fields. To provide good service, IT Service Management is implemented. Service Management can provide value to be implemented by companies, one of which is by implementing the ITIL framework which consists of several services but in this journal will focus on Service Operations. The research method applied is qualitative research which analyzes the data in depth. From the results of the research conducted, it is known that there are several companies that have not implemented Service Operations optimally, even so Service Operations still have a role within the company. The processes contained in Service Operations such as Event Management, Problem Management, Incident Management, Request Fulfillment, and Access Management have an important role so that the systems within the company's companies run according to the goals and wishes of customers, there are implementations made to assess IT service operations which will show the maturity level of existing processes, some create strategies using Customer Relationship Management, some create SOPs using the PDCA method, and some implement Service Operations by improving services.